Agricultural commercialisation through innovation platforms: a case for goat production - Modiba, Mothupi (Graduate School of Business (GSB), 2021)
Empirical evidence has shown that goats are of significance in marginalised, poor, and rural economies and this information has been well documented in scholarly research. Despite its importance and potential contribution, goat farming remains underutilised and undeveloped in the rural economy - particularly in South Africa. Developmental intervention has focused on improving productivity with minimal effort aimed at the integration of key role players in the value chain, and even less emphasis on improving farmers' attitudes. The largest goat population in South Africa is found in the Northern Cape where there is great potential to be realised for goat farming. The main objective of this study was to identify supply side (production) factors constraining subsistence goat production in South Africa, with the view of identifying key actors to establish an innovation platform through vertical integration. By transforming the subsistence farming orientation of goat farmers into a commercial (market) orientation, the welfare of communities can be improved through the commercialisation of smallscale goat farmers. Studies highlight the need to enhance goat production beyond subsistence goat rearing and towards commercialisation through access to markets, veterinary services, credit facilities, and government support. Furthermore, a focus on market development, value chain integration and innovation platforms can improve the efficiency of the goat farming sector. This study contributes to the existing body of knowledge on goat farming in South Africa and offers an innovation platform to foster partnerships among the actors along the value chain, creating an enabling environment for the easy flow of market information and infrastructure development. A praxis model is incorporated into this research. This takes the form of a business model and is provided in Appendix B as a practical way of applying the knowledge gathered in this research.